Novel systems biology insights using antifibrotic approaches for diabetic kidney disease. Issue 1 (January 2010) - RamachandraRao, Satish P; Talwar, Priti; Ravasi, Timothy; Sharma, Kumar
Although several interventions slow the progression of diabetic nephropathy, current therapies do not halt progression completely. Recent preclinical studies suggested that pirfenidone (PFD) prevents fibrosis in various diseases, but the mechanisms underlying its antifibrotic action are incompletely understood. To explore the therapeutic potential of PFD, we studied the PFD-treated db/db diabetic mouse kidney by liquid chromatography–tandem mass spectrometry proteomics. A total of 21 proteins unique to PFD-treated diabetic kidneys were identified. Analysis of gene ontology and protein–protein interactions of these proteins suggested that PFD may regulate RNA translation. Two key proteins involved in mRNA translation initiation and elongation were further evaluated and found to be regulated by PFD at the level of phosphorylation. In conclusion, insights from combining proteomics and bioinformatics improve the likelihood of rapid advancement of novel clinical therapies focused on reducing inflammation and fibrosis for diabetic complications.